Mean platelet volume is increased in patients with chronic hepatitis B - Demir, Canan; Demir, Mehmet (The European Research Journal, 2016)
Background. Hepatitis secondary to infection with the hepatitis B virus (HBV) is one of the most common causes of viral hepatitis worldwide. Multiple extrahepatic manifestations of HBV infection have been recognized. However, the effect of HBV infection on the mean platelet volume (MPV) is unknown. The aim of this study was to assess the MPV, an indicator of platelet activation, in patients with chronic hepatitis B. Methods. The study group consisted of 50 patients with chronic hepatitis B. An age, gender, and body mass index-matched control group consisted of 50 healthy volunteers. All patients and control participants underwent echocardiographic examination. We measured the serum MPV values in patients and control participants. Results. Mean platelet volume was significantly higher among patients with HBV when compared with the control group (9.2±2.2 vs 7.1±1.6 fl, respectively; p<0.001). Conclusion. We have shown that MPV was significantly elevated in patients with chronic hepatitis B compared to control participants. According to our knowledge, there has been no previous study of MPV in chronic HBV patients. Therefore, we have investigated the possible association between HBV infection and MPV.